Decoding the inferior vena cava - Pérez Cateriano, Víctor (2018)
Nowadays ultrasonography is a very important tool for intensive care physicians, the use of which is spreading more and more. However, it is not enough to acquire the technical skills to perform it, but also -and perhaps more importantly- we must know how to interpret the findings, for which an adequate knowledge of physiology or underlying pathophysiology is critical. Such is the case of understanding the mechanisms or forces involved in the distension and collapse of the inferior vena cava, in order to provide an adequate clinical application to the images we get when we analyze this variable.